Outcome of Surgery as Sole Treatment of Eosinophilic Granuloma of Jaws - Saeed Nezafati; Javad Yazdani; Shahriar Shahi; Mahsa Mehryari; Emran Hajmohammadi (Shiraz University of Medical Sciences, 2019)
Langerhans cell histiocytosis (LCH) is characterized by the congregation of proliferating langerhans cells (LC). Langerhans cells are a part of dendritic cell system of primary immune response that is responsible for presenting antigen to lymphocytes. Being a rare disease, the total incidence of LCH is reported to be 1 in 2 million people. LCH mainly affects children and young adults, with a slight male predilection. LCH is clinically divided into three groups namely Letter-Siwe disease (multiple multi organ affecting LCH at very young age), Hand-Schuler-Christian disease (LCH of bone involvement exophthalmos and diabetes insipidus), and Eosinophilic granuloma (LCH of bone, solitary or multiple). The extent of involvement influences the treatment planning. In this retrospective study, we survey five patients with eosinophilic granuloma in jaws (bony LCH). The diagnosis was confirmed by tissue biopsy and histopathologic examination. Surgery and curettage of the lesions were carried out under general or local anesthesia. After surgery, the patients were examined clinically every 6 month in the first year and then once in a year. The overall outcome was excellent. According to the results, it can be concluded that surgical curettage of localized eosinophilic granuloma is an appropriate and sufficient treatment.